Principal (Ac.Ency Theory Perspective) Reviewed From Java Scara (HANACARAKA) - Mahsuni, Abdul Wahid (Budapest International Research and Critics University, 2021)
The purpose of this research is to find out how the principal as the owner of the company gives his trust to the manager based on the values contained in the Javanese script. The analysis of the data used is HANAC'ARAKA which reflects that humans are the image of God who in nature has creativity, taste and intention, which is a unity in the sense that there is a universe of God and humans where one cannot be separated from one another. The principal in Javanese culture is as a representative of God in front of the earth and carries out a mandate from God in the form of property which must be used according to His instructions, and the use of property by the principal is not for the benefit of the individual but for the benefit of the community. The use of assets must have a meaning, namely the emphasis on the use of resources, namely all these activities are useful for the community which as a whole can bring prosperity and welfare. This is clearly revealed in a word to make Hayuning Bawana beautify or decorate the world, thus we contribute to saving the world, so that humans carry out their roles in the world by fulfilling their obligations, among others, to work. As a reflection of God's representative in front of the burni principal as a trustee from God.